The Influence of Democratic Leadership Style, Compensation and Work Environment on Employee Performance: Pengaruh Gaya Kepemimpinan Demokratis, Kompensasi dan Lingkungan Kerja terhadap Kinerja Karyawan - Anggraeni, Leni; Sumartik, Sumartik (Indonesian Journal of Law and Economics Review, 2023)
This study applies a quantitative method with hypothesis testing. The sample used in this study is the entire population of 55 employees UD. Ratu Kencana Pangan Cabang Ngerong Kecamatan Gempol. The analytical tool used in this research is multiple linear regression analysis using SPSS version 22 for windows. The primary data in this study were obtained from a questionnaire whose measurement was using a Likert scale which was tested for validity and reliability. The results of this study prove that leadership style democratic partially has a positive effect on employee performance. Compensation partially has a positive effect on employee performance. The work environment partially has a positive effect on employee performance. Leadership style democratic, compensation, and work environment simultaneously have a positive and significant effect on employee performance.